Penerapan Layanan Prima untuk Meningkatkan Kepuasan Pelanggan dalam Perspektif Pemasaran Syariah: (Studi Kasus Di Toserba Sunan Drajat Cabang Lasem) - Elvidatul Mubariroh; Syamsir Alamsyah Harahap; Kurnia Cahya Lestari (Al-Musthofa: Journal of Sharia Economics, 2026)
This study aims to determine the implementation of excellent service to increase customer satisfaction based on a sharia marketing perspective at Sunan Drajat Department Store, Lasem Branch. The research focuses on the implementation of excellent service, the implementation of sharia marketing values, and their impact on customer satisfaction. This study uses a qualitative approach with field research methods to obtain in-depth data. Data were obtained through interviews, observations, and documentation of managers, employees, and customers. The results show that excellent service is implemented through fast, accurate, friendly service, and a comfortable environment. Sharia marketing values ​​are also implemented through honesty, trustworthiness, fairness, good communication, and the provision of halal products. These implementations have a positive impact on customer satisfaction because customers feel comfortable, trustworthy, and satisfied when shopping.